Detrimental Effect of Type I IFNs During Acute Lung Infection With Pseudomonas aeruginosa Is Mediated Through the Stimulation of Neutrophil NETosis - Pylaeva, Ekaterina; Bordbari, Sharareh; Spyra, Ilona; Decker, Anna Sophie; Häussler, Susanne; Vybornov, Vadim; Lang, Stephan; Jablonska, Jadwiga (Frontiers in Immunology, 2019)
Pseudomonas aeruginosa is an opportunistic multidrug-resistant pathogen, able to grow in biofilms. It causes life-threatening complications in diseases, which are characterized by the up-regulation of type I interferon (IFN) signaling, such as cancer or viral infections. Since type I IFNs are known to regulate multiple functions of neutrophils that constitute the first line of anti-bacterial host defense, in this work we aimed to study how interferon-activated neutrophils influence the course of P. aeruginosa infection of the lung. After infection, we observed significantly elevated bacteria load in WT mice, accompanied by the prominent lung tissue damage, while IFN-deficient animals seem to be partly resistant to the infection. Lung neutrophils from such IFN-deficient animals release significantly lower amounts of neutrophil extracellular traps (NETs) and reactive oxygen species (ROS), as compared to WT neutrophils. Such IFN-deficient neutrophils show significantly decreased capacity to stimulate biofilm formation by P. aeruginosa. Reduced biofilm production impairs the survival of bacteria in a lung tissue. In line with that, treatment with recombinant IFN- enhances neutrophil NETosis and stimulates biofilm formation by Pseudomonas after co-incubation with such neutrophils. Possibly, bacteria utilizes neutrophil-derived NETs as a scaffold for released biofilms. In agreement with this, in vivo treatment with ROS-scavengers, NET disruption or usage of the bacterial strains unable to bind DNA suppress neutrophil-mediated biofilm formation in the lungs. Together, our findings indicate that the excessive activation of neutrophils by type I IFNs leads to their boosted NETosis that in turn triggers biofilm formation by P. aeruginosa and supports its persistence in the infected lung. Targeting these mechanisms could offer a new therapeutic approach to prevent persistent bacterial infections in patients with diseases associated with the up-regulation of type I IFNs.